Development of Caesarean Section Clinical Pathway: A Lesson Learned - Sastrawan, I Gede; Wardhani, Viera (Fakultas Kedokteran Universitas Brawijaya, 2021)
Although clinical pathway (CP) is aimed to ensure quality and cost, the development of CP at hospitals is primarily for administrative purposes as it is required by accreditation standards, thus causing high variations in its implementation. This study aimed to develop a clinical pathway for caesarean section and explore the problem during development and implementation test. The selection of caesarean section was based on high volume, risk, and cost. Using participatory action research, the researcher started the program by performing an implementation evaluation, literature review, and regulatory development. The evaluation identified implementation discrepancies and prolonged length of stay. Based on the evaluation and literature review results, the Professional Care Provider (PCP) in the hospital conducted discussions and made suggestions by considering available resources, current practices, and behavior. The main differences of the new clinical pathway are: 1) it is developed based on literature and current practice, and 2) it should be added with notification, explanation, inclusion and exclusion criteria, and references. Before the implementation test, the hospital provide resources, develops a standard operational procedure followed by monitoring and evaluation. Differences in the type of medication and documentation method were found, which then further discussed with all involved PCP to define the agreed solutions. Professional engagement and openness culture that embraces along the process are the main key lesson learned in addition to the understanding that CP development and implementation is a continuous learning process.